STUDY ON THE HISTORY OF INDIAN ENGLISH NOVELS - Tathagat (International Journal of Multidisciplinary Research and Studies, 2021)
The Indian English novel, which had begun its voyage with the publication of Bankim Chandra Chatterjee's Rajmohan's Wife, went through a significant transformation in terms of its style and theme throughout the course of time. The Calcutta Literary Gazette and Saturday Evening Hurkaru were two of the first publications that included the germ of an idea for an Indian book written in English. The earliest attempts at writing a novel were KylashChunderDutt'sA Journal of 48 Hours of the Year 1945, which was published in The Calcutta Literary Gazette in 1835, and ShosheeChunderDutt's Republic of Orissa: Annals from the Pages of the Twentieth Century, which was published in The Saturday Hurkaru in 1845. However, these works were more like short stories than novels in their own right. Only after Bankim Chandra Chatterjee's Rajmohan's Wife, the first and only novel written in English by Chatterjee, was published in the Calcutta weekly, The Indian Field, in serialised form and then finally got published in book form in 1935 did the real journey begin. Rajmohan's Wife was Chatterjee's only novel written in English. Writers from Bengal and subsequently Madras played a significant part in the early stages of the creation of the English novel, beginning in the 1860s and continuing until the end of the nineteenth century. Among them, it is important to highlight the contributions of Bankim Chandra Chatterjee, Romesh Chandra Dutt, Toru Dutt, and Rabindranath Tagore from Bengal, as well as A. Madhaviah and T. Ramakrishna Pillai from Madras. Their literary style was mostly derivative, or we might say that it was westernised; it was primarily influenced by British writers working in the previous and current eras, and the issues that they focused on were socio-historical in nature.